Pengembangan Ekonomi Wanita Nelayan Pesisir Pantai Pulau Raam Melalui Pengolahan Produk Perikanan - Ratna Ratna; Sulfiana Sulfiana; Muh Arzad; Riman Sangaji; Muna Muna; Asni Anwar; Kamaluddin Kamaluddin; Ahmad Fahrizal (Abdimas: Papua Journal of Community Service, 2023)
This service aims to build understanding and knowledge of female fishermen in the coastal area of ​​Raam Island regarding economic development through fishery products that are marketed with a marketing diversification system. Partners in Community Service (PkM) are fisherwomen on Raam Island, Sorong Islands District, Sorong City, Southwest Papua Province. The lack of understanding and information obtained by fishermen and fisherwomen makes them sell the fish they get, most of it is sold in fresh form and some is processed into dried fish. So that the income received is also little or even no income. So that in its development, marketing diversification is needed which will increase the economic value of fishery products. The results of the Community Service Program that has been carried out on partners is that partners' insight and understanding of the material provided increases, especially handling fishery products boldly using social media.